THE EFFECT OF DIFFERENT CONCENTRATIONS OF PHYTOHORMONES ON THE GROWTH AND YIELD OF SWEET CORN (Zea mays sturt L.) - Jannah, Raudatul; Sari, Mella Mutika; Istyadji, Maya (Transpublika Publisher, 2022)
This study aims to determine the growth and yield of sweet corn based on the concentration of phytohormones sprayed day and night. As well as to find out which concentration of phytohormones gives the best effect on the parameters of plant height, number of leaves, age of flowering, fruit weight, and number of fruit. This study used a two-factor completely randomized design (CRD). The first factor of phytohormone concentrations consisted of T0 = 0 ml/L, T1 = 6 ml/L, T2 = 8 ml/L, T3 = 10 ml/L, T4 = 12 ml/L with 3 repetitions and 27 experimental units. The subject of this research is phytohormone and the object of this research is sweet corn of bonanza F1 variety. Collecting data in this study is by direct observation and documentation. Data were analyzed by ANOVA (Analysis of Variance) followed by the DMRT test if there was an effect. Based on the results of the DMRT test, treatment T4 = 12 ml/L had an effect on plant height and fruit weight with values of 195.4 cm and 162 grams, respectively. Treatment T3 = 10 ml/L had an effect on the number of leaves with a value of 18.7 and treatment T1 = 6 ml/L had an effect on the age of flowering with a value of 46.2 HST. The best phytohormone administration is produced from the administration of phytohormone which is sprayed during the day.